Space and territory from an anthropological perspective. The case of the Purhépechas of Nurío and Michoacán in Mexico - Álvaro Bello (CUHSO)
This article analyses some theoretical perspectives about the categories of territory and spacein indigenous contexts. To do this it attempts to review the traditional perspectives which link territory,political practice and ethnicity in indigenous contexts. The problem is addressed from the perspective ofpolitical anthropology and territorial geography, and takes as an example the case of the Purhépechas ofMichoacán in Mexico. The development of this case is important for the subject of territory, since Michoacánand the Purhépechas have been a real “laboratory” of Mexican and North American anthropology for theapplication of concepts and focuses such as “area studies”, “refuge regions” or “indigenous regions”. Thisaccounts for the relevance of an analysis which reviews and questions the assumptions which have been atthe base of these categorisations, starting from a perspective which is more centred on the subjects, theirway of life, and how they represent space and territory.